Psychometric evaluation of the short form of the Arizona Life History Battery (K-SF-42): A revised Chinese version for emerging adults. (2nd November 2020) - Zhang, Meng Xuan; Hui, Bryant P. H.; Wu, Anise M. S.
Life history (LH) strategies explain how organisms adapt to the environment and make the best use of their resources to fulfill bodily maintenance, growth, reproduction and other functions. The K-SF-42 is a short version of the 199-item Arizona Life History Battery for assessing seven different domains of LH strategies. This article aims to evaluate the psychometric properties of a Chinese version of the K-SF-42. We recruited 1, 016 Chinese university students, who aged 16 to 28 years old ( M age = 19.47, SD = 1.17) to participant in an anonymous questionnaire. Results of the confirmatory factor analysis supported the second-order six-factor model (except romantic partner attachment), and the scale and subscales of such measurement displayed good internal consistencies. With the exception of religiosity, all of the subscales showed significant positive correlations with a brief unidimensional measure of LH strategies (i.e., the Mini-K). The criterion-related validity of the scale was further supported by the association between its higher score (suggesting slower LH strategies) and the lower levels of childhood harshness and unpredictability. This study provided evidence for the satisfactory applicability of the Chinese version of the K-SF-42 to a Chinese population and contributed to the further investigation of the LH strategies' mechanisms underlying human behavior across cultures.